Targeting drugs to tumours using cell membrane-coated nanoparticles - Fang, Ronnie H; Gao, Weiwei; Zhang, Liangfang (Nature reviews. Clinical oncology, 2023)
Traditional cancer therapeutics, such as chemotherapies, are often limited by their non-specific nature, causing harm to non-malignant tissues. Over the past several decades, nanomedicine researchers have sought to address this challenge by developing nanoscale platforms capable of more precisely delivering drug payloads. Cell membrane-coated nanoparticles (CNPs) are an emerging class of nanocarriers that have demonstrated considerable promise for biomedical applications. Consisting of a synthetic nanoparticulate core camouflaged by a layer of naturally derived cell membranes, CNPs are adept at operating within complex biological environments; depending on the type of cell membrane utilized, the resulting biomimetic nanoformulation is conferred with several properties typically associated with the source cell, including improved biocompatibility, immune evasion and tumour targeting. In comparison with traditional functionalization approaches, cell membrane coating provides a streamlined method for creating multifunctional and multi-antigenic nanoparticles. In this Review, we discuss the history and development of CNPs as well as how these platforms have been used for cancer therapy. The application of CNPs for drug delivery, phototherapy and immunotherapy will be described in detail. Translational efforts are currently under way and further research to address key areas of need will ultimately be required to facilitate the successful clinical adoption of CNPs.